Development of Interactive Multimedia Using Android-based Ispring Suite and Integrated Webquiz Kahoot for Temperature and Heat Material - Rosana Yulia; Endang Surahman; Nana Nana (Jurnal Ilmiah Pendidikan Fisika, 2023)
Research on the development of interactive multimedia using Android-based Ispring Suite and integrating Webquiz Kahoot on temperature and heat material, which aims to analyze the level of validity and practicality of the developed multimedia. The research was conducted using the R&D method through a 4-D model (Define, Design, Development, and Disseminate). However, this research is limited to the development stage because it is focused on knowing the level of validity and practicality of the product. The definition stage includes front-end analysis, analysis of student needs, and formulation indicators of competence attainment. The design stage includes making an outline, a flowchart, and a storyboard, choosing a supporting platform, and selecting the type of writing. The development stage includes making products, conducting validation tests by material and media expert validators, and conducting practical tests involving XI IPA 1 and XI IPA 3 classes as research subjects and high school physics educators. The results showed that the validation results for material experts and media experts were 0,94 and 0,92 in the very valid category, while the average percentage of practicality was 97,5% in the very practical category. The developed interactive multimedia can be used in the learning process on temperature and heat material for class XI IPA, and it is hoped that using this multimedia can improve student learning outcomes.